2016
DOI: 10.1093/carcin/bgw068
|View full text |Cite
|
Sign up to set email alerts
|

Glioma-mediated microglial activation promotes glioma proliferation and migration: roles of Na+/H+exchanger isoform 1

Abstract: Microglia play important roles in extracellular matrix remodeling, tumor invasion, angiogenesis, and suppression of adaptive immunity in glioma. Na(+)/H(+) exchanger isoform 1 (NHE1) regulates microglial activation and migration. However, little is known about the roles of NHE1 in intratumoral microglial activation and microglia-glioma interactions. Our study revealed up-regulation of NHE1 protein expression in both glioma cells and tumor-associated Iba1(+) microglia in glioma xenografts and glioblastoma multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 56 publications
(85 reference statements)
2
46
0
Order By: Relevance
“…All these cell lines were developed through SV40 immortalization of human primary microglial cells, whereas a fraction of SV40-immortalized adult microglial cells were further engineered to express the human telomerase reverse transcriptase (hTERT) and reduce the proliferation rate [19]. To the best of our knowledge, two cell lines are commercially available, the human microglial clone 3 cell line, HMC3 [17,[20][21][22] and the "Immortalized Human Microglia -SV40", developed and distributed by Applied Biological Materials (Vancouver, Canada) [23][24][25][26][27][28]. The HMC3 has been recently authenticated by the American Type Culture Collection (ATCC®), a leading nonprofit organization in the authentication and distribution of biologic material, microorganisms, and standards.…”
Section: Introductionmentioning
confidence: 99%
“…All these cell lines were developed through SV40 immortalization of human primary microglial cells, whereas a fraction of SV40-immortalized adult microglial cells were further engineered to express the human telomerase reverse transcriptase (hTERT) and reduce the proliferation rate [19]. To the best of our knowledge, two cell lines are commercially available, the human microglial clone 3 cell line, HMC3 [17,[20][21][22] and the "Immortalized Human Microglia -SV40", developed and distributed by Applied Biological Materials (Vancouver, Canada) [23][24][25][26][27][28]. The HMC3 has been recently authenticated by the American Type Culture Collection (ATCC®), a leading nonprofit organization in the authentication and distribution of biologic material, microorganisms, and standards.…”
Section: Introductionmentioning
confidence: 99%
“…NHE1 plays an important role in regulating microglial intracellular pH (pH i ) homeostasis, their activation, and migration (Boscia et al, 2016;Liu et al, 2010;Shi et al, 2013;Zhao et al, 2016;Zhu et al, 2016). In particular, NHE1 maintains optimal pH i to support NADPH oxidase (NOX) function during microglial activation (Lam et al, 2013).…”
mentioning
confidence: 99%
“…Upregulation of the Na + /H + exchanger isoform 1 (NHE1), leading to increased intracellular sodium and increased intracellular pH, has been implicated in promoting glioma proliferation, invasion and resistance to temozolomide therapy[24, 25]. Another study demonstrated that in oligodendrogliomas, IDH-mutated and 1p/19q codeleted, the NHE1 on 1p is silenced, and proposes that this could be a major contributor to the low proliferation rates in these tumors[26].…”
Section: Discussionmentioning
confidence: 99%